Optimization Of Mild Chamber For The Combustion Of Biomass Producer Gas - Moustafa Hebish, Anas Ahmed Moustafa Moustafa (Universiti Sains Malaysia, 2022)
Energy production still heavily relies on combustion. MILD combustion is a promising candidate to support the transition towards the net zero emission target, however it needs further fundamental study due to the current limited research on its application on low-grade biomass producer gas (PG). The main challenge is to achieve complete combustion in MILD combustion with low CO and NOx emissions while maintaining simple and compact combustor geometry. The aim of this study was to tackle the challenges of low-grade biomass producer gas (PG) through optimization of MILD combustion. The work included using ANSYS-FLUENT computational fluid dynamics (CFD) simulation of low-grade biomass producer gas (PG) from wood air-gasification in a MILD combustion chamber. The study included two stages of Design of Experiments (DOE), first-stage (DOE1) and second-stage (DOE2). Geometry parameters, for two shapes (circular cross-section and square cross-section combustors) were tested by using 18 CFD simulation cases and results were analysed through DOE1 optimization tool. Optimum geometry for circular combustors was 200mm in combustor diameter, Dc and 1000mm in combustor length, Lc with 710°C maximum temperature increase, 3.3 ppm CO emissions, 15.2 ppm NOx emissions and 0.99 Damköhler number and the optimum geometry for square combustors was 548.86mm combustor length, Ls and 1500mm combustor height, Hs with 718°C maximum temperature increase, 6.41 ppm CO emissions, 342.24 ppm NOx emissions and 0.34 Damköhler number. The circular combustors significantly surpassed the square ones in, terms of performance, for CO and NOx emission and Damköhler number with the exception of maximum temperature increase. DOE2 involved the optimum circular combustor since circular combustors generally outperformed the square combustors and had better optimum combustor characteristics. DOE2 had 9 CFD simulations based on the instruction of DOE. DOE2 aimed to optimize the MILD combustion chamber for operating conditions. In the end , the circular cross-section combustor of 200mm in combustor diameter, Dc and 1000mm in combustor length, Lc with fuel-air equivalence ratio, φ = 0.9 and fuel inlet velocity, Vf = 200m/s having 733°C maximum temperature increase, 2.5 ppm CO emissions, 11.1 ppm NOx emissions and 0.76 Damköhler number was considered the optimum MILD chamber.